The effectiveness of patient navigation programs for adult cancer patients undergoing treatment: a systematic review. (February 2016) - Tho, Poh Chi; Ang, Emily
Executive summary : Background : Advancements in technology and medical treatment have made cancer care treatment more complex. With the current trend of sub‐specialization in health care, cancer patients commonly receive care from multiple specialists and have wider treatment options. In view of this, there is a need to coordinate care and integrate information to enhance care and quality of outcomes for patients. Since the successful implementation of programs for increasing the survival rate of breast cancer patients at Harlem Hospital Center, New York, USA, patient navigation programs have been widely introduced in healthcare settings. Some literature has identified nurses as a primary candidate in assuming the role of a navigator. However, there is a need to further explore the effectiveness of patient navigation programs for their effectiveness in improving quality of life, and patient satisfaction and outcomes during the commencement of cancer treatment. Objectives : The objective of this review was to synthesize the best available evidence on the effectiveness of patient navigation programs in adult cancer patients undergoing treatments such as radiotherapy and/or chemotherapy. Inclusion criteria : Types of participants This review considered studies that included adults aged 18 years and over, diagnosed with any type of cancer and undergoing treatment in an acute care hospital setting, including inpatient and outpatient/ambulatory care. Types of intervention(s) and comparator(s) This review considered studies that evaluated nurse‐led patient navigation programs versus no patient navigation program or non‐structured care coordination. A patient navigation program includes patient education, psychosocial support, and care coordination. Types of studies This review considered randomized controlled trials and quasi‐experimental studies. Types of outcomes The review focused on the effects of patient navigator program clinical/patient outcomes. The review included studies on patient wellbeing and clinical outcomes, but excluded studies that had examined the impact of these programs on efficiency‐related outcomes, such as length of hospital stay and resource use. Search strategy : A three‐step search strategy was utilized to find both published and unpublished studies in the databases: CINAHL, MEDLINE, Academic Search Complete, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Science Direct, Google Scholar (SCIRUS), MEDNAR (first 200 hits) and ProQuest Dissertations and Theses published between 1990 to 2013. Only studies published in English were included in this review. Methodological quality : Two reviewers independently evaluated the methodological quality of studies that met the inclusion criteria for the review, using a standardized critical appraisal instrument from the Joanna Briggs Institute. Data extraction : Data was extracted from the included papers using the standardized data extraction tool from the Joanna Briggs Institute Meta‐Analysis of Statistics Assessment and Review Instrument. Data synthesis : Quantitative data was pooled in a statistical meta‐analysis using Review Manager 5.3. Effect sizes expressed as weighted mean differences (for continuous data) and their 95% confidence intervals were calculated for analysis. Heterogeneity was assessed statistically using the standard Chi‐square test. Where statistical pooling was not possible, the findings are presented in narrative form. Results : After the process of study selection, four studies (two randomized controlled trials and two quasi‐experimental studies) with a total of 667 participants were included in the review. The results demonstrated no statistically significant difference in the quality of life of patients with cancer who had undergone patient navigation programs (pooled weighted difference = 0.41 [95% CI = ‐2.89 to 3.71], P=0.81). However, the two included studies that assessed patient satisfaction as an outcome measure both showed statistically significant improvements (p‐values = 0.03 and 0.001, respectively). In the study that assessed patient distress level, there was no statistically significant difference found between the: nurse‐led navigation and non‐navigation groups (P = 0.675). Conclusions : Nurse‐led patient navigation programs were not effective in addressing outcomes such as quality of life and distress levels, the systematic review did not find any significant difference between the two groups. However, there was a statistically significance difference in increasing patient satisfaction. Implications for practice There is limited evidence that patient navigation programs improve the outcomes of quality of life and reduce distress (for adult patients with cancer undergoing treatment). However, there is good evidence that patient navigation programs improve patients' satisfaction. Therefore it is recommended that patient navigation programs are used for adult cancer patients in the acute care setting to improve patients' satisfaction. Implications for research There may be a need to explore a more rigorous evaluation of nurse‐led navigation programs to determine their effectiveness. Researchers should consider multi‐site studies and larger sample sizes for better generalization.